Development of Financial Markets in Central Europe : The Case of the CE4 Countries - Adarov, Amat (IMF Working Papers; Working Paper, 2011)
Financial markets in the CE4 countries are still shallow compared to other advanced EU countries. While the government bond markets are comparable in size, measured by capitalization in percent of GDP, the private bond, private credit, and equity markets lag behind. Empirical analysis in this paper helps identify factors that explain this phenomenon. We find that the observed differences cannot be explained by macroeconomic variables only, but incorporating indicators of institutional development and external funding eliminates the gap in the case of the equity and private credit markets. However, for the private bond market a significant gap remains even after accounting for these factors.